KERABAT SEBAGAI MESIN POLITIK: KLIENTELISME DAN KEMENANGAN KANDIDAT PEREMPUAN PEMULA PADA PEMILU LEGISLATIF DPRD KABUPATEN NAGEKEO TAHUN 2024 - Gadhe, Maria Kristiana; Subekti, Valina Singka (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to analyze how kinship-based clientelism influences the victory of female novice candidates in a political space that tends to be dominated by a patriarchal system. The research findings indicate that in the context of Maria Roswita Mea Laki's victory, the role of the nuclear family, a campaign team consisting of relatives, and the provision of social assistance were very dominant, which in turn strengthened local community solidarity in gaining voter support. In addition, the role of Mosalaki (traditional leaders) provided important symbolic legitimacy, as did cadet/farmer groups that served as low-cost mobilization arenas based on social solidarity at the village level. These social networks contributed significantly to the campaign's success, particularly in the context of the Nagekeo community, which remains strongly tied to family and customary ties. This study utilizes Herbert Kitschelt's (2000) theory of clientelism and social networks.